1,5-Phosphonium betaines from N-triflylpropiolamides, triphenylphosphane, and active methylene compounds - Fiore, Vito A.; Freisler, Chiara; Maas, Gerhard (Beilstein Journal of Organic Chemistry, 2019)
N-Phenyl-N-(trifluoromethylsulfonyl)propiolamides react with triphenylphosphane in the presence of various active methylene compounds CH2XY in a 1:1:1 molar ratio to furnish 1-phosphonium-5-oxabetaines, Ph3P+–C(R)=CH–C(O–)=CXY. These betaines are formed preferentially, but not exclusively, as E-diastereoisomers with respect to the vinylic double bond. In some cases, separation of the two diastereoisomers was achieved by fractionating crystallization. Structure determination by X-ray diffraction analysis revealed marked conformational differences around the CH–C(O–) single bond of E and Z-isomers and extended charge delocalization in the anionic part.
Keywords: betaines; multi-component reactions; N-triflylamides; phospha-Michael reaction; propiolamides

(untitled) - Guo, H.; Fan, Y. C.; Sun, Z.; Wu, Y.; Kwon, O. (Chem. Rev., 2018)

(untitled) - Enders, D.; Saint-Dizier, A.; Lannou, M.-I.; Lenzen, A. (Eur. J. Org. Chem., 2006)

(untitled) - Ye, L.-W.; Zhou, J.; Tang, Y. (Chem. Soc. Rev., 2008)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Ramazani, A.; Kazemizadeh, A. R.; Ahmadi, E.; Noshiranzadeh, N.; Souldozi, A. (Curr. Org. Chem., 2008)

(untitled) - Stoddard, R. L.; Luo, J.; van der Wal, N.; O'Rourke, N. F.; Wulff, J. E.; McIndoe, J. S. (New J. Chem., 2014)

(untitled) - Nagao, K.; Yamazaki, A.; Ohmiya, H.; Sawamura, M. (Org. Lett., 2018)

(untitled) - Zi, Y.; Schömberg, F.; Seifert, F.; Görls, H.; Vilotijevic, I. (Org. Biomol. Chem., 2018)

(untitled) - Yavari, I.; Maghsoodlou, M. T. (Tetrahedron Lett., 1998)

(untitled) - Yavari, I.; Anary-Abbasinejad, M.; Alizadeh, A. (Phosphorus, Sulfur Silicon Relat. Elem., 2002)

(untitled) - Yavari, I.; Islami, M. R.; Bijanzadeh, H. R. (Tetrahedron, 1999)

(untitled) - Shaabani, A.; Teimouri, M. B.; Yavari, I.; Arasi, H. N.; Bijanzadeh, H. R. (J. Fluorine Chem., 2000)

(untitled) - Heydari, R.; Maghsoodlou, M. T.; Yami, R. N. (Chin. Chem. Lett., 2009)

(untitled) - Ghodsi, F.; Habibi-Khorassani, S. M.; Shahraki, M. (Molecules, 2016)

(untitled) - Zhu, X.-F.; Henry, C. E.; Kwon, O. (J. Am. Chem. Soc., 2007)

(untitled) - Liu, H.; Zhang, Q.; Wang, L.; Tong, X. (Chem. – Eur. J., 2010)

(untitled) - Deng, J.-C.; Chan, F.-W.; Kuo, C.-W.; Cheng, C.-A.; Huang, C.-Y.; Chuang, S.-C. (Eur. J. Org. Chem., 2012)

(untitled) - Fiore, V. A.; Maas, G. (Tetrahedron, 2019)

(untitled) - Fiore, V. A.; Maas, G. (Z. Naturforsch., B: J. Chem. Sci., 2019)

(untitled) - Hennig, L.; Alva-Astudillo, M.; Mann, G.; Kappe, T. (Monatsh. Chem., 1992)

(untitled) - Bordwell, F. G.; Branca, J. C.; Bares, J. E.; Filler, R. (J. Org. Chem., 1988)

(untitled) - Hendrickson, J. B.; Bergeron, R. (Tetrahedron Lett., 1973)

(untitled) - Brown, R. F. C.; Eastwood, F. W. (Synlett, 1993)

(untitled) - Masters, A. P.; Sorensen, T. S.; Tran, P. M. (Can. J. Chem., 1987)

(untitled) - Saijo, R.; Uno, H.; Mori, S.; Kawase, M. (Chem. Commun., 2016)

(untitled) - Kawamoto, I.; Hata, T.; Kishida, Y.; Tamura, C. (Tetrahedron Lett., 1971)

(untitled) - Kawamoto, I.; Hata, T.; Kishida, Y.; Tamura, C. (Tetrahedron Lett., 1972)

(untitled) - Naya, S.-i.; Nitta, M. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Duncan, M.; Gallagher, M. J. (Org. Magn. Reson., 1981)

(untitled) - Espenlaub, S.; Gerster, H.; Maas, G. (ARKIVOC, 2007)

(untitled) - Albright, T. A.; Freeman, W. J.; Schweizer, E. E. (J. Am. Chem. Soc., 1975)